2022
DOI: 10.48550/arxiv.2203.03650
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kitaev spin-orbital bilayers and their moiré superlattices

Abstract: We determine the phase diagram of a bilayer, Kitaev spin-orbital model with inter-layer interactions (J), for several stackings and moiré superlattices. For AA stacking, a gapped Z2 quantum spin liquid phase emerges at a finite Jc. We show that this phase survives in the well-controlled large-J limit, where an isotropic honeycomb toric code emerges. For moiré superlattices, a finite-q inter-layer hybridization is stabilized. This connects inequivalent Dirac points, effectively 'untwisting' the system. Our stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
2
0
0
Order By: Relevance
“…While our results for small values of J/K agree with Ref. [86], we successfully capture the effect of the varying stacking arrangement on the intralayer hopping, which was neglected in other works. We have shown that such terms allow one to isolate flat from dispersive bands.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…While our results for small values of J/K agree with Ref. [86], we successfully capture the effect of the varying stacking arrangement on the intralayer hopping, which was neglected in other works. We have shown that such terms allow one to isolate flat from dispersive bands.…”
supporting
confidence: 89%
“…While preparing this manuscript, we became aware of a related work [86]. While our results for small values of J/K agree with Ref.…”
supporting
confidence: 84%